2022
DOI: 10.1108/imr-03-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

How knowledge acquisition creates a competitive edge? A qualitative inquiry from international consultancy alliance

Abstract: PurposeThe current study attempts to bridge the existing gap related to the role of knowledge acquisition from international alliance partners to improve competitiveness by examining the distinct processes of knowledge acquisition and the challenges confronted in this learning process in order to enhance local and international market performance.Design/methodology/approachFollowing case-study approach based on systematic combining, the study presents a case of knowledge acquisition and learning in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 130 publications
(252 reference statements)
0
20
0
Order By: Relevance
“…Finally, extant literature has revealed that skilled and knowledgeable employees are more likely to exert directed effort towards work-related activities and achieve a high level of performance (Appelbaum et al, 2000;Tsai et al, 2007;Aslam, et al, 2022). Moreover, highly skilled and knowledgeable workers seek new ways to complete tasks, which enhances their agility in the workplace (Holotiuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, extant literature has revealed that skilled and knowledgeable employees are more likely to exert directed effort towards work-related activities and achieve a high level of performance (Appelbaum et al, 2000;Tsai et al, 2007;Aslam, et al, 2022). Moreover, highly skilled and knowledgeable workers seek new ways to complete tasks, which enhances their agility in the workplace (Holotiuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the identification of knowledge and utilization can help the organization in achieving a competitive advantage (Nonaka, Toyama, & Nagata, 2000). The acquisition of knowledge is very important to gain a competitive edge for firms within the country and even across borders (Aslam, Ali, Qammar, Kiwan, & Dhir , 2022).…”
Section: Acquisition Of New Knowledgementioning
confidence: 99%
“…Operational Level Management Capabilities (OLBDMC) and Knowledge Creation Knowledge is a vital resource for firms and can be upgraded with the use of big data along with managerial skills (Khalil & Belitski, 2020) and to remain differentiated in the market by improving themselves through knowledge sharing with developed countries (Aslam, Ali, Qammar, Kiwan, & Dhir, 2022). The knowledge creation and its sharing among peers and downward to operational team is very important for hotel industry (Kankam-Kwarteng, Osei, Asante-Gyabaah, & Ferkah, 2022).…”
Section: Development Of Hypotheses 31mentioning
confidence: 99%